2018
DOI: 10.1177/0894439318774856
|View full text |Cite
|
Sign up to set email alerts
|

An APPetite for APPs: A Comparison of Heavily Reliant and Light Reliant App Users on Political Activity and Media Reliance

Abstract: The ubiquity of mobile devices and the apps that power them has spurred concerns that they are contributing to the decline in news media use. Mobile devices, however, have been credited with spurring political participation. In its examination of app-reliant individuals, this study found that reliance on apps positively predicts political participation, and respondents who rely heavily on mobile apps for political information are more politically active than light app users on six of the seven measures of nono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results provide novel empirical evidence of the statistically significant positive association of mobile media information use and democratic outcomes in sub-Saharan Africa, in this instance measuring attitudes about support for the watchdog role of journalism. These findings align with the literature that tends to find mobile media diffusion and increased news use as consistently positively associated with individuals’ increased desire for indicators of stronger democracy by allowing citizens to experience democratic norms, values, and practices such as free expression (Kaye & Johnson, 2019; J. A. Martin, 2014; Mattes & Bratton, 2007; Park & Gil de Zúñiga, 2019, 2021; Stoycheff & Nisbet, 2014).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results provide novel empirical evidence of the statistically significant positive association of mobile media information use and democratic outcomes in sub-Saharan Africa, in this instance measuring attitudes about support for the watchdog role of journalism. These findings align with the literature that tends to find mobile media diffusion and increased news use as consistently positively associated with individuals’ increased desire for indicators of stronger democracy by allowing citizens to experience democratic norms, values, and practices such as free expression (Kaye & Johnson, 2019; J. A. Martin, 2014; Mattes & Bratton, 2007; Park & Gil de Zúñiga, 2019, 2021; Stoycheff & Nisbet, 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Baek and Kim (2016) found that mobile media usage for information and e-commerce purposes was positively related to political information-seeking and political discussion, while relational mobile uses had a negative relationship, and entertainment uses produced no relationship. And in investigating frequency and intensity of use, Kaye and Johnson (2019) found that mobile app users who relied more heavily on mobile media for political information were more politically active than lighter app users. These patterns of individual mobile media adoption also have been found to have direct implications for societal-level indicators such as compressing the global mobile divide (Chang et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have found a direct connection between news consumption and political participation, and it follows that individuals who rely heavily on mobile apps for news are also likely to participate in both offline and online political activities (Gil de Zúñiga et al, 2017; Kaye & Johnson, 2019; Ohme, 2020; Yamamoto & Nah, 2018; Yoo et al, 2016). Further, app users who express their political views are also more likely to participate in political activities than those who use apps simply as a way of finding information (Valeriani & Vaccari, 2018; Yamamoto et al, 2015, 2018).…”
Section: Reliance On Discussion As a Mediatormentioning
confidence: 99%
“…The analyses are carried out and assessed according to the suggestion of Kaye and Johnson (2019, 2020). Moreover, in the hierarchical regression process, the study also evaluates the variance inflation factors (VIFs) if they are less than 10, indicating no multicollinearity issues with the data and results (Hair et al, 2006).…”
Section: Methodsmentioning
confidence: 99%